Penggunaan Modul MMFE untuk Meningkatkan Efikasi Diri Bahasa Inggris Siswa SMP - Arfi Nurul Hidayah; Asmadi Alsa (Faculty of Psychology, Universitas Gadjah Mada, 2016)
The differences of subject load and limited ability of students in learning English give uncertainty to student of class VII in studying it. Uncertainty themselves (self-efficacy) could decrease the willingness of the students to gain expected achievement. This study aims to examine the effect of using Mind mapping Module for English (MMFE) in improving student's English self-efficacy on class VII. This research is a module validation through the method of quasi experimental design with untreated control group design with pretest and posttest dependent samples. The subjects were 31 students of class VII. Collecting data using english self-efficacy scale, comprehension test as manipulation checks, and MMFE module. Aiken's V statistic test was used to test the validity coefficient contents of module, while the mixed anova test was used to test the effect of MMFE module towards english self-efficacy. The result showed MMFE module valid by content and empiric to improving english self-efficacy of class VII students (F=5,433, p<0,05).